Public Relations Strategy of PDAM Tirtawening in Responding to Consumer Complaints through Social Media (Twitter) - Anisa Nurul Hasanah; Elsa Yuniarti; Dasrun Hidayat (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this study is to find out how PDAM Tirtawening's public relations strategy in responding to consumer complaints during the Covid-19 pandemic. After the Covid-19 pandemic, there were many changes ranging from social changes, community behavior actions, to changes in public services, especially in Pdam Tirtawening Bandung. This study uses descriptive studies with a skin-skinned approach. Data collection techniques in this study are observations, in-depth interviews with informants that have been determined by researchers consisting of 3 informants. Based on system theory by defining problems, planning and programming, communicating, evaluating this study found the fact that PDAM Tirtawening's Public Relations strategy during the Covid-19 pandemic is still receiving complaints, although the complaint is only submitted through social media twitter therefore PDAM Tirtawening strives as quickly as possible to respond to complaints and problems.